Efisiensi Biaya dalam Perawatan Stroke Non-Hemoragik: Studi Kasus di Rumah Sakit Islam Sunan Kudus - Mubarok, Chusnul; Suryawati, Chriswardani; Harto, Puji (UI Scholars Hub, 2024)
Stroke is one of the leading causes of morbidity and mortality globally, with over 12 million new cases each year. In Indonesia, the prevalence of stroke increased from 8.3% in 2007 to 12.1% in 2013, with the age group of 55-64 years recording the highest prevalence. This study aims to analyse the actual costs of non-hemorrhagic stroke care for patients under the National Health Insurance (JKN) at the Islamic Hospital of Sunan Kudus using the Activity-Based Costing (ABC) method. A descriptive quantitative method was applied, collecting data from hospitalised non-hemorrhagic stroke patients during 2023. The results showed a discrepancy between actual costs and INA-CBGs tariffs, with the average actual cost reaching Rp3.146.184, which is lower than the hospital tariff of Rp5.762.965 and the INA-CBGs tariff of class iii Rp4.036.200. CRR1 reaching 183.13% indicates that the hospital tariff includes unit costs with a significant surplus. Meanwhile, CRR2 at 128.30% shows that the INA-CBGs tariff also covers actual costs, but with a smaller margin. This discrepancy financially burdens the hospital, especially for class 3 patients. This study recommends evaluating the hospital's tariff structure and improving compliance with clinical pathways to enhance cost efficiency and service quality. Thus, applying the ABC method is expected to provide more accurate cost information and support more effective management of BPJS claims.